Cutting technique structure using explosive shape charge / Rozanizam Abdul Razak and Abdul Aziz Mansor - Abdul Razak, Rozanizam; Mansor, Abdul Aziz (2002)
Decommissioning of an offshore structure nowadays, has become one of the most important issues since the emerging of oil and gas industries. This industry has become the most profitable sector and lead towards the development of economic, social and infrastructure in the country. The increment in the number of platform build for the propose of oil and gas drilling also indicate the growth of this industry. Apart from it the number of old platforms also increase and have to be removed as stated in the off shore law. The cutting techniques used in decommissioning process are very important since it may give bad effect to the environment and sea mammals. Reliability and cost of the decommissioning process also important to be considered when we are choosing the best techniques.The latest technique in decommissioning process is the use of explosive in cutting techniques. These techniques have become important nowadays since they are more reliable, effective, efficiency and cheap. Although these techniques can promise all these good things but they still give bad effects to the environment and sea life. Research must be done to increase the capability of these techniques and at the same time reduce the bad effects to environment and sea life. Objective of this project is to survey and collecting information on current trend on decommissioning of offshore structure. The use of shaped charge is being focused in this project since it can produce a good and smooth cutting on the target. The ability of this technique has made it become one of the most suitable to be used for under water cutting. It also can reduce the cost of decommissioning since it use only few equipment compared to the mechanical or abrasive cutting technique..